Bioremediation of arable soil using Nitrogen, Phosphorus, Potassium fertilizer treatment - Ekenwosu Joseph Ugochukwu (Sustinere: Journal of Environment and Sustainability, 2019)
This study seeks to examine â€œin situâ€ remediation effectiveness of NPK fertilizer treatment as a viable biostimulation-based bioremediation technology for soil remediation by evaluating data obtained from soil physicochemical properties before and after initiation of bioremediation. Bioremediation was initiated by stimulating indigenous microorganisms in soil by NPK application while remediation was determined by soil physicochemical condition after nutrient amendment and changes observed in plant height after 60, 90, 120, 150, 180 and 210 days of planting. Rhizomes of turmeric were planted in soil treated with NPK fertilizer and control in a randomized complete block design (RCBD) with three replications. Data generated from soil physicochemical parameters in laboratory and field was analyzed before and after treatment. Study showed increase in available potassium, available phosphorus, total nitrogen, pH, cation exchange capacity (CEC) and organic carbon. However, there was decrease in aluminium, soil organic matter and acidity. Sand, silt and clay also decreased slightly. Study revealed significant increase in plant height from plants that benefitted from nutrient amendment.